PENDAMPINGAN TEKNIS BUDIDAYA BAWANG MERAH PADA MASYARAKAT SUKU NAULU DI NEGERI NUANEA KECAMATAN AMAHAI KABUPATEN MALUKU TENGAH - Kesaulya, Henry; Nuruwe, Fransiska Edels; Laisina, Jane Kathryne; Jambormias, Edizon; Matatula, Erfina Anace Matatula; Syauta, Franklin; Latuheru, Elsye; Laipa, Ridwan; Abataman, Ester; Maitimu, Helfina Betsyane (MAANU: Jurnal Pengabdian Kepada Masyarakat, 2025)
The Naulu Tribe in Nuanea Village, Central Maluku, in their efforts to develop shallots face obstacles in cultivation. These obstacles include lack of knowledge about proper cultivation techniques, limited access to technology and information, and difficulties in marketing the harvest. This community service program aims to improve the knowledge and skills of the Naulu Tribe in Nuanea Village in shallot cultivation, and is expected to increase community income and welfare. This program is implemented through collaboration between students and lecturers of the Plant Breeding Study Program, Faculty of Agriculture, Pattimura University and the Parakletos Maluku Foundation. This program involves technical training in shallot cultivation and field assistance. Training materials include shallot seed nursery techniques and proper cultivation, pest and disease control, and processing of ready-to-plant seeds. This program can improve the knowledge and skills of the Naulu Tribe in Nuanea Village in shallot cultivation and especially the provision of ready-to-plant seedlings from seeds. This community service program has a significant positive impact on the Naulu Tribe in Nuanea Village. Collaboration between students, lecturers of the Faculty of Agriculture, Plant Breeding Study Program and the Parakletos Maluku Foundation in this program shows the importance of synergy to achieve optimal results in community empowerment. This program can be a model for other community service programs that aim to improve the welfare of people in remote areas.